2010
DOI: 10.5194/angeo-28-479-2010
|View full text |Cite
|
Sign up to set email alerts
|

Severe geomagnetic storms and Forbush decreases: interplanetary relationships reexamined

Abstract: Abstract. Severe storms (Dst) and Forbush decreases (FD) during cycle 23 showed that maximum negative Dst magnitudes usually occurred almost simultaneously with the maximum negative values of the B z component of interplanetary magnetic field B, but the maximum magnitudes of negative Dst and B z were poorly correlated (+0.28). A parameter B z (CP) was calculated (cumulative partial B z ) as sum of the hourly negative values of B z from the time of start to the maximum negative value. The correlation of negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 26 publications
1
42
0
Order By: Relevance
“…Belov et al (2001) and Kane (2010) maintain that there is a reasonable correlation between the FD magnitude and the product of maximum magnetic field and maximum solar wind velocity. Dumbović et al (2012) also found reasonable correlation A&A 580, A41 (2015) detectors (each 1 m 2 ), with a distance of 8 m between adjacent detectors deployed in a hexagonal geometry (Gupta et al 2005;Mohanty et al 2009;Mohanty et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Belov et al (2001) and Kane (2010) maintain that there is a reasonable correlation between the FD magnitude and the product of maximum magnetic field and maximum solar wind velocity. Dumbović et al (2012) also found reasonable correlation A&A 580, A41 (2015) detectors (each 1 m 2 ), with a distance of 8 m between adjacent detectors deployed in a hexagonal geometry (Gupta et al 2005;Mohanty et al 2009;Mohanty et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Thus the interest to the measurements of positrons and antiprotons is increasing. Important finding was done by PAMELA experiment (Adriani et al, 2009;2010). The authors present data on the positron abundance in the CR in the energy range 1.5 -100 GeV with high statistics.…”
Section: Lecr Variationsmentioning
confidence: 95%
“…Mustajab and Badruddin (2011) critically analyze the differences in geoeffectiveness due to different structures and features, with distinct plasma/field characteristics. Distinct relations of FDs and geomagnetic activity measured by Dst in different events is reported by (Kudela and Brenkus, 2004;Kane, 2010). Richardson and Cane (2011) analyzed large number of ICMEs and their associated shocks passing the Earth during years 1995 -2009.…”
Section: Irregular Variationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sporadic Forbush decreases of the GCR intensity are associated with major solar flares. These Forbush decreases can be caused by (1) shock and ejecta, (2) shock only or (3) ejecta only [33]. Sporadic Forbush decreases generate drops of the order of 5-10% at 10 GV rigidity.…”
Section: Forbush Decreasesmentioning
confidence: 99%